Atomistic analysis to characterize the impact of temperature and defects on the mechanical properties of germanene sheet. (30th January 2018) - Paul, R; Tasnim, T; Saha, S; Motalab, M
Abstract: Germanene, a monolayer buckled hexagonal form of germanium shows surprisingly superior electrical and physical properties in strained and defected form. However, mechanical characterization and effects of chirality, temperature, and defects on mechanical properties of germanene are yet to be comprehensively investigated. An attempt is made in this study using the application of molecular dynamics simulation with the optimized tersoff potential to analyze the uniaxial tensile properties of germanene sheet. The room temperature ultimate strength of pristine 152 Å × 152 Å zigzag and armchair germanene sheet is estimated to be 7.9 GPa and 6.8 GPa, respectively. A negative correlation of ultimate strength and fracture strain with temperature is found. Additionally, four types of structural defects were introduced in the germanene sheet namely; point vacancy, bi-vacancy, Stone–Wales (SW) types 1 and 2. Regarding bi-vacancy, the ultimate strength decreases substantially in both armchair and zigzag direction compared to point vacancy whereas the effect of SW defects shows chirality dependency. A SW-1 defect accounts for a larger decrease in ultimate strength in armchair direction than in zigzag direction where a reversed trend follows in SW-2 defect.